The Use of Arabic Language by Teachers in General English Classes in Libya: Elementary and Intermediate Learners - Younes, Najla M. (Al-Mukhtar Journal of Social Sciences, 2021)
This study was led to make sense of the mentalities of Arabic Libyan EFL students towards the use of mother tongue in their English classes. Forty-five elementary level students and thirty-five pre-intermediate level students at two English circles around Albayda City, Libya, were approached to round out a twelve-item survey adjusted from specialized. The outcome uncovered that the understudies of both English levels have positive answers towards their L1 utilizing in L2 classes as a beneficial method to give further clarification on troublesome syntax focuses and the befuddled jargon’s implications.